PERTANGGUNGJAWABAN KORPORASI TERHADAP TINDAK PIDANA SUAP BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PERUBAHAN UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Nadya Alika Jely; Erdianto Effendi; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Corporate criminal action in the case of bribery offense, basically is an act that is carried out by directors and / or corporate employees, at every level that carries out their duties and functions and can represent the corporation, which can result in criminal liability. Both to the corporation and together with its employees personally, criminal liability can be held. The modus operandi of bribery is carried out directly and indirectly in various forms. The reason and the purpose of corporations to make bribes is to maximize profits and survive global competition, as well as the reasons for extortion carried out by certain officials, officials or bodies or protection of corporations that conduct illegal business. This bribery crime is regulated in Law Number 20 of 2001 concerning Amendment of Law No. 31 of 1999 concerning Eradication of Corruption. This research uses the typology of normative legal research or also called doctrinal legal research, which more specifically discusses the principles of legal law. In this study the authors used the nature of descriptive research, because the authors describe the Corporate Liability Against Bribery Based on Law No. 31 of 1999 Concerning Eradication of Corruption.The results of the research conducted by the author are, Corporations must be held liable for criminal liability because the corporation as the maker and at the same time responsible is because the profits obtained by the corporation or the losses suffered by the public can be so great and the bribery crime by the corporation has the main motive is in the interests of the corporation itself and can be another source of crime. Judges should impose additional criminal sanctions on corporations as stipulated in Article 18 of Law Number 20 of 2001 concerning Amendment of Law Number 31 of 1999 concerning Eradication of Corruption, there are various obstacles, including the problem of proving mistakes in imposing crimes and absence of additional crimes.Keywords: Liability - Corporation- Criminal Act - Bribe